Overexpression of WNT16 Does Not Prevent Cortical Bone Loss Due to Glucocorticoid Treatment in Mice - Alam, Imranul (JBMR Plus, 2018)
Glucocorticoids (GC) are commonly used for the treatment of a wide variety of autoimmune, pulmonary, gastrointestinal, and malignancy conditions. One of the devastating side effects of GC use is osteoporotic fractures, particularly in the spine and hip. Bisphosphonates (BP) are the most commonly prescribed pharmacological agents for the prevention and treatment of GC‐induced osteoporosis (GIO). However, GIO is marked by reduced bone formation and BP serves mainly to decrease bone resorption. The WNT signaling pathway plays a major role in bone and mineral homeostasis. Previously, we demonstrated that overexpression of WNT16 in mice led to higher bone mineral density and improved bone microarchitecture and strength. We hypothesized that WNT16 overexpression would prevent bone loss due to glucocorticoid treatment in mice. To test our hypothesis, we treated adult wild‐type and WNT16‐transgenic mice with vehicle and GC (prednisolone; 2.1 mg/kg body weight) via slow‐release pellets for 28 days. We measured bone mass and microarchitecture by dual‐energy X‐ray absorptiometry (DXA) and micro‐CT, and performed gene expression and serum biochemical analysis. We found that GC treatment compared with the vehicle significantly decreased femoral areal bone mineral density (aBMD), bone mineral content (BMC), and cortical bone area and thickness in both wild‐type and transgenic female mice. In contrast, the trabecular bone parameters at distal femur were not significantly changed by GC treatment in male and female mice for both genotypes. Further, we observed significantly lower level of serum P1NP and a tendency of higher level of serum TRAP in wild‐type and transgenic mice due to GC treatment in both sexes. Gene expression analysis showed lower mRNA levels of Wnt16, Opg, and Opg/Rankl ratio in GC‐treated female mice for both genotypes compared with the sex‐matched vehicle‐treated mice. These data suggest that although WNT16 overexpression resulted in higher baseline bone mineral density and bone volume per trabecular volume (BV/TV) in the transgenic mice, this was insufficient to prevent bone loss in mice due to glucocorticoid treatment. © 2018 The Authors JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.